Food aid: An effective instrument of development policy? - Siegfried Schultz (Intereconomics, 1987)
After over thirty years experience with food aid, there is consensus only on its use as a means of mitigating acute distress; except with regard to disaster relief of that kind, opinions are divided on the rationale of food aid deliveries from industrial countries with a food surplus to Third World countries with a deficit. What are the main arguments for and against food aid, and in which direction has the EC's food aid programme developed?
Keywords: 330; North-South Relations